Comparison of paroxetine and amitriptyline in the treatment of refractory globus pharyngeus. Issue 9 (September 2016) - Chen, Dong-yun; Jia, Lin; Gu, Xi; Jiang, Shu-man; Xie, Hai-li; Xu, Jian
Abstract: Background: Clinical trials of antidepressants for treatment of globus are generally rare, let alone for refractory globus pharyngeus. Aims: To illustrate the efficacy and side-effects of antidepressants between paroxetine and amitriptyline for refractory globus patients. Methods: Refractory globus patients were randomized into paroxetine group; amitriptyline group and lansoprazole group for 6-week treatment. All the subjects were asked to complete the following questionnaires pre- and post-therapy: Glasgow Edinburgh Throat Scale (GETS), Pittsburgh Sleep Quality Index, Hamilton Rating Scale Anxiety/Depression and Medical outcome short-form 36. Treatment response was defined as a >50% reduction in the GETS score. Results: One hundred and forty-eight patients completed the study. After 6 week treatment, 71.7% of paroxetine group (33/46) were calculated as treatment response, significantly higher than that in amitriptyline group (46.2%, 24/52) and lansoprazole group (14.0%, 7/50). Compared with lansoprazole group or amitriptyline group, a more distinct improvement of emotional well-being, quality of life and quality of sleep were observed in paroxetine group after 6-week treatment. Conclusion: Paroxetine therapy is more efficacious than empirical high-dose antisecretory treatment, or even the low-dose amitriptyline therapy in alleviating globus symptoms, and producing global improvements for refractory globus patients.